2001
DOI: 10.1007/pl00000786
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-rich proteins as structural components of plant cell walls

Abstract: Glycine-rich proteins (GRPs) have been found in the cell walls of many higher plants and form a third group of structural protein components of the wall in addition to extensins and proline-rich proteins. The primary sequences of GRPs contain more than 60% glycine. GRPs are localized mainly in the vascular tissue of the plant, and their coding genes provide an excellent system to analyze the molecular basis of vascular-specific gene expression. In French bean, the major cell wall GRP has been localized at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
1
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(177 citation statements)
references
References 65 publications
6
164
1
6
Order By: Relevance
“…In the C-terminal part of the sequence, 10 repeated Gly-rich sequences were clustered, separated by several hydrophilic sequences of eight to 19 amino acids. In land plants, extensins are Hyp-rich proteins present in the extracellular matrix, where they are thought to play a role in plant cell wall stiffness (Kieliszewski and Lamport, 1994), and Glyrich proteins are secreted proteins involved in adhesion and extension of differentiating vascular cells (Ringli et al, 2001).…”
Section: Morphogenetic Mutants Are Altered In the Auxin Perception Anmentioning
confidence: 99%
“…In the C-terminal part of the sequence, 10 repeated Gly-rich sequences were clustered, separated by several hydrophilic sequences of eight to 19 amino acids. In land plants, extensins are Hyp-rich proteins present in the extracellular matrix, where they are thought to play a role in plant cell wall stiffness (Kieliszewski and Lamport, 1994), and Glyrich proteins are secreted proteins involved in adhesion and extension of differentiating vascular cells (Ringli et al, 2001).…”
Section: Morphogenetic Mutants Are Altered In the Auxin Perception Anmentioning
confidence: 99%
“…Molecular biology techniques and the complete sequencing of the Arabidopsis thaliana genome greatly contributed to the description of many CWP gene families and their transcriptional regulation [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It was found that most CWP are encoded by multigene families.…”
Section: Towards a More Comprehensive View Of Cell Wall Proteinsmentioning
confidence: 99%
“…The anther development gene ATA20 (At3g15400; group D) was identified previously as stamen specific (Rubinelli et al, 1998). It encodes a protein containing a Gly-rich region that is characteristic of one of the groups of cell wall proteins (Sachetto-Martins et al, 2000; Ringli et al, 2001). The second gene encodes an arabinogalactan protein, AGP6 (At5g14380; group D).…”
Section: Cell Wall-associated Gene Productsmentioning
confidence: 99%